(3efgLjI GdHMK GdYdej aj GdYdhe GdEfSGfjI h GdELJeGYjI (B/s - (3SHJj, QTjOIs ((3GdLRGFQ (B:s (3OGQ GdJfhjQ ,s, 2014)
(3jYJHQ GdHMK GdYdej ef GdhSGFd GdJj JbGS HgG JWhQ GdGee h GdeLJeYGJ fXQG dOhQg aj OQGSI GdhGbY h ageg h GdhUhd Gdi GdMdhd HWQjbI YdejI (B.(3ceG Gf JWhQ GdHMhK GdYdejI eQJHW HOQLI GdGgJeGe GdJj JhdjgG dg eNJda GdeASSGJ GdeLJeY h Pdc HJhajQ eQGcR h eNGHQ GdHMhK h JRhjOgG HGMOGK GdJbfjGJ h GdhSGFd h JTLjY GdHGMKjf eGOjG h eYfhjG h JhXja eG JJhUd dg gPg GdHMhK ef fJGFL h GdGSJaGOI efgG dage GdeLJeY (B. (3Gf eUOGbjI fJGFL GdHMhK GdYdejI eQghfI aj GdefgLjI GdeJHYI GKfGA GdbjGe HGdHMK aj XGgQI eLJeYjI eG dPdc LGA GdcJGH HeG jMJhjg ef eYdheGJ Mhd cjajI GdHMK HWQjbI efgLjI UMjMI dGLd GdhUhd Gdi fJGFL UGObI h ObjbI hhGbYjIs
Keywords: (3GdHMK GdYdejs; (3GdYdhe GdEfSGfjI h GdELJeGYjIs; (3efgLjI GdHMK GdYdejs